Endocrine and immune responses to resistance training in prostate cancer patients - Galvao, D; Nosaka, K; Taaffe, D; Peake, J; Spry, N; Suzuki, K; Yamaya, K; McGuigan, M; Kristjanson, Linda; Newton, R (Nature Publishing Group, 2008)
This study examined the effect of 20 weeks resistance training on a range of serum hormones and inflammatory markers at rest, and following acute bouts of exercise in prostate cancer patients undergoing androgen deprivation. Ten patients exercised twice weekly at high intensity for several upper and lower-body muscle groups. Neither testosterone nor prostate-specific antigen changed at rest or following an acute bout of exercise. However, serum growth hormone (GH), dehydroepiandrosterone (DHEA), interleukin-6, tumor necrosis factor-alpha and differential blood leukocyte counts increased (P < 0.05) following acute exercise. Resistance exercise does not appear to compromise testosterone suppression, and acute elevations in serum GH and DHEA may partly underlie improvements observed in physical function.